Partial melting due to breakdown of an epidote‐group mineral during exhumation of ultrahigh‐pressure eclogite: An example from the North‐East Greenland Caledonides. (25th September 2018) - Cao, Wentao; Gilotti, Jane A.; Massonne, Hans‐Joachim; Ferrando, Simona; Foster, Charles T.
Abstract: In the North‐East Greenland Caledonides, P–T conditions and textures are consistent with partial melting of ultrahigh‐pressure (UHP) eclogite during exhumation. The eclogite contains a peak assemblage of garnet, omphacite, kyanite, coesite, rutile, and clinozoisite; in addition, phengite is inferred to have been present at peak conditions. An isochemical phase equilibrium diagram, along with garnet isopleths, constrains peak P–T conditions to be subsolidus at 3.4 GPa and 940°C. Zr‐in‐rutile thermometry on inclusions in garnet yields values of 820°C at 3.4 GPa. In the eclogite, plagioclase may exhibit cuspate textures against surrounding omphacite and has low dihedral angles in plagioclase–clinopyroxene–garnet aggregates, features that are consistent with former melt–solid–solid boundaries and crystallized melt pockets. Graphic intergrowths of plagioclase and amphibole are present in the matrix. Small euhedral neoblasts of garnet against plagioclase are interpreted as formed from a peritectic reaction during partial melting. Polymineralic inclusions of albite+K‐feldspar and clinopyroxene+quartz±kyanite±plagioclase in large anhedral garnet display plagioclase cusps pointing into the host, which are interpreted as crystallized melt pockets. These textures, along with the mineral composition, suggest partial melting of the eclogite by reactions involving phengite and, to a large extent, an epidote‐group mineral. Calculated and experimentally determined phase relations from the literature reveal that partial melting occurred on the exhumation path, at pressures below the coesite to quartz transition. A calculated P–T phase diagram for a former melt‐bearing domain shows that the formation of the peritectic garnet rim occurred at 1.4 GPa and 900°C, with an assemblage of clinopyroxene, amphibole, and plagioclase equilibrated at 1.3 GPa and 720°C. Isochemical phase equilibrium modelling of a symplectite of clinopyroxene, plagioclase, and amphibole after omphacite, combined with the mineral composition, yields a P–T range at 1.0–1. 6 GPa, 680–1, 000°C. The assemblage of amphibole and plagioclase is estimated to reach equilibrium at 717–732°C, calculated by amphibole–plagioclase thermometry for the former melt‐bearing domain and symplectite respectively. The results of this study demonstrate that partial melt formed in the UHP eclogite through breakdown of an epidote‐group mineral with minor involvement of phengite during exhumation from peak pressure; melt was subsequently crystallized on the cooling path.